Archives for the Lay Person: A Guide to Managing Cultural Collections - Hamill, Lois (Rowman & Littlefield Publishers, 2012)
For volunteers or staff at small organizations, collections management can be a daunting task. Archives for the Lay Person is a guidebook for people who care for historical records, photographs, and collections but do not have the appropriate professional training. Lois Hamill provides practical, step-by-step guidance for managing all facets of archival collections, from acquisition, arrangement, and description to storage and security. The book also offers advice on how to utilize PastPerfect software for collections database management.